The influence of intensive anaerobic effort on the rhythm of movement - Skowronek, T.; Juras, G.; Slomka, K. J. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To estimate the influence of global anaerobic fatigue on rhythm performance. Methods: Fifteen young males participated in the experiment. Anaerobic fatigue was induced with 2 consecutive running-based anaerobic sprint tests (RAST). The level of lactate was controlled before the first RAST and 3 minutes after each RAST. The rhythm performance was assessed by using Optojump Next (Microgate, Bolzano, Italy). The rhythm test was conducted 3 times, before fatigue and immediately after each RAST. Eight variables of the rhythm test were analyzed: the mean frequency of jumps for the assisted and unassisted phase (XfAP and XfUAP), SD of jump frequency for the assisted and unassisted phase (SDfAP and SDfUAP), and mean absolute error for the assisted and unassisted phases of the test (XERAP and XERUAP, respectively). Results: One-way repeated-measures analysis of variance showed a significant main effect of anaerobic effort on rhythm variables only in the unassisted phase of the test. Statistically significant differences were observed in XfUAP between the first and third rhythm measurements (F2,28 = 4.98, P < .014, eta2p=26.23%), SD of jump frequency for the unassisted phase (SDfUAP; F2,28 = 3.48, P = .05, eta2p=19.9%), and mean absolute error for the unassisted phase (XERUAP; F2,28 = 3.36, P = .006, eta2p=19.43%). Conclusions: The results show that rhythm of movement may be negatively influenced after intensive anaerobic fatigue. The exact mechanism of this phenomenon is not precisely defined, but both central and peripheral fatigue are suspected to be involved.